Development of the circumduction metric for identification of cervical motion impairment. (May 2018) - Zhou, Yue; Loh, Eldon; Dickey, James P; Walton, David M; Trejos, Ana Luisa
Introduction: Chronic neck pain results in considerable personal, clinical, and societal burden. It consistently ranks among the top three pain-related reasons for seeking healthcare. Despite its prevalence, neck pain is difficult to both assess and treat. Quantitative approaches are required since diagnostic imaging techniques rarely provide information on movement-related neck pain, and most common clinical assessment tools are limited to single plane motion measurement. Methods: In this study, the ability of an inertial measurement unit to document the cervical motion characteristics of 28 people with chronic neck pain and 23 healthy controls was assessed. A total of six circumduction metrics and one neck circumduction trajectory model were proposed as identification metrics. Results: Five metrics demonstrated significant differences between the two groups. The neck circumduction trajectory model successfully distinguished between the two groups. Discussion: The evaluation of the proposed metrics provides proof of concept that novel metrics can be captured with relative ease in the clinical setting using an inexpensive wearable sensor headband. The derivation of the proposed model may open new lines of inquiry into the clinical utility of assessing the multiplanar movement of cervical circumduction. The results obtained from this study also provide additional insight for the development of a sensitive, quantifiable and real-world neck evaluation strategies.